Multi-wavelength Brillouin-Raman fiber laser generation assisted by multiple four-wave mixing processes in a ring cavity - Shirazi, M.R.; Taib, J.M.; Dimyati, K.; Harun, Sulaiman Wadi; Ahmad, Harith (IOP Publishing, 2013)
A multi-wavelength Brillouin-Raman fiber laser (MBRFL) is generated by using a 7.7?km long dispersion compensating fiber which acts as both the Brillouin and Raman gain media. The MBRFL is pumped at 16?dBm with two Raman pumps at 125?mW. Eleven Stokes and anti-Stokes lines are generated with a line spacing of about 0.155?nm (~19.86?GHz) without any forward line reflection. By combining the backward and forward outputs, more lines can be generated, with narrower line spacings of about 0.077?nm (~9.93?GHz). The number of lines can be increased by having higher Brillouin and Raman pump powers. Since Raman amplification can be arranged at any wavelength region, the MBRFL can be obtained at any wavelength as long as all of the equipment and components are prepared in the proposed operational wavelength region.